2014
DOI: 10.3109/14992027.2013.873956
|View full text |Cite
|
Sign up to set email alerts
|

Benefit from non-linear frequency compression hearing aids in a clinical setting: The effects of duration of experience and severity of high-frequency hearing loss

Abstract: NLFC was beneficial for consonant recognition but not speech recognition in noise. There was no evidence to support the idea that a long period of acclimatization is necessary to gain full benefit. The relation between benefit and high-frequency thresholds might be explained by the poor audibility of compressed information for some listeners with severe loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 22 publications
3
41
3
Order By: Relevance
“…This is in contradiction with another study where it was found that NFC does not improve sentence recognition in noise and that there is no significant correlation between the NFC benefit and period of acclimatization [5]. The study by Wolfe and colleagues [8] did however find that the benefit from NFC (both for consonant recognition and sentence intelligibility in noise) was greater following six months after the initial fit.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This is in contradiction with another study where it was found that NFC does not improve sentence recognition in noise and that there is no significant correlation between the NFC benefit and period of acclimatization [5]. The study by Wolfe and colleagues [8] did however find that the benefit from NFC (both for consonant recognition and sentence intelligibility in noise) was greater following six months after the initial fit.…”
Section: Discussioncontrasting
confidence: 55%
“…The study by Wolfe and colleagues [8] did however find that the benefit from NFC (both for consonant recognition and sentence intelligibility in noise) was greater following six months after the initial fit. It should be noted that the study by [5] included adult participants with a mean age of 75 years whereas the participants in the current study is much younger (aged 20 to 69 years) and that the study by Wolfe et al [8] included children compared to adults in the current study. Clearly, this continues to be an area of interest and future research should focus hereon to establish the clinical significance of the benefit of NFC in noise and with extended use.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consonant sound detection in speech recognition in quiet environments, but not in noisy conditions, was significantly better when FC was activated. No significant correlation between time of FC experience and its benefits was found (22) . No study has investigated the period of acclimatization required to achieve fullest advantage of FC.…”
Section: Introductionmentioning
confidence: 89%
“…Findings are mixed on the effect of NFC relative to RBW on speech recognition and potential relationships are complex (Alexander, 2013; Alexander et al, 2014; Arehart et al, 2013; Bentler et al, 2014; Ching et al, 2013; Ellis & Munro, 2015; Glista et al, 2009; Glista et al, 2012; Hopkins et al, 2014; John et al, 2014; Kokx-Ryan et al, 2015; McCreery et al, 2013, 2014; Picou et al, 2015; Simpson et al, 2005, 2006; Souza et al, 2013; Wolfe et al, 2010, 2011, 2015). In general, benefit from NFC is better when access to high frequency sounds is increased with NFC (McCreery et al, 2013, 2014) but spectral distortion is minimized (Souza et al, 2013) as well as in listeners with greater high-frequency hearing loss (Brennan et al, 2014; Glista et al, 2009; Souza et al, 2013; but see Kokx-Ryan et al, 2015).…”
Section: Speech Recognitionmentioning
confidence: 99%